VALIDITY OF THE INHERITANCE DEED IN THE CASE OF ABSENCE OF ONE OF THE HEIRS - Salsabila Aisyah Putri; Dinda Alfira Syahrani; Adit Hartadi; Chintia Natasya; Sanusi Sanusi (Ann Publisher, 2025)
Abstract: Background. Inheritance is an important aspect of civil law related to the transfer of rights to a person's property after death. The inheritance process involves not only the division of property but also the rights and obligations of the heirs who are left behind. Aims. This study aims to analyze the validity of inheritance deeds in the context of one of the heirs' absence and identify the mechanisms for protecting their rights. The title of this study was chosen because the absence of heirs often triggers inheritance disputes that require legal certainty. Methods. By using a qualitative approach and a juridical-normative method to the relevant articles in the Civil Code (KUHPerdata), including Articles 490-492, Article 1024, as well as a study of the Supreme Court Decision No. 2180K/Pdt/2017, the Central Jakarta District Court Decision No. 1447/Pid.B/2016/PN.Jkt.Pst, and Article 49 of Law No. 3 of 2006 concerning Religious Courts. Result. The results of the study indicate that inheritance deeds remain valid even if they do not involve all heirs, as long as the notary has carried out adequate verification and the rights of the absent heirs are recognized. Conclusion. This study also found that the right to think given to heirs and the authority of the Religious Court to determine the status of heirs contribute to legal certainty in the inheritance process. Implementation. Thus, this study provides an overview of how the legal system in Indonesia provides flexibility in making inheritance deeds as long as the principles of justice and legal certainty are met.